Food addiction and preoperative weight loss achievement in patients seeking bariatric surgery. (23rd October 2018) - Guerrero Pérez, Fernando; Sánchez‐González, Jéssica; Sánchez, Isabel; Jiménez‐Murcia, Susana; Granero, Roser; Simó‐Servat, Andreu; Ruiz, Ana; Virgili, Nuria; López‐Urdiales, Rafael; Montserrat‐Gil de Bernabe, Mónica; Garrido, Pilar; Monseny, Rosa; et al.
Abstract: Introduction: Evidence suggests that food addiction (FA) is prevalent among individuals with obesity seeking bariatric surgery (BS), but there is no evidence about whether FA is a predictor of weight loss (WL). We aimed to analyse the prevalence of FA in patients with obesity seeking BS and to examine whether FA could predict WL following dietary intervention before surgery. Method: The study included 110 patients with obesity who underwent a dietetic intervention. Assessment included endocrinological variables, a semistructured interview to rule out mental disorders, and Yale Food Addiction Scale version 2.0 (YFAS 2.0). Results: In our sample, the prevalence of FA was 26.4%. Those who met YFAS 2.0 criteria showed less WL after dietetic intervention and regain weight during dietary intervention. Conclusions: FA appears to be prevalent in obesity. Our findings confirmed a lower WL throughout dietary intervention before surgery in patients who fulfilled baseline criteria for FA. Future interventions should include multidisciplinary intervention to maximize WL before and after BS.